TRANSFIGURASI SOSIAL AGAMA MASYARAKAT PASCA PENDIRIAN BANDAR UDARA INTERNASIONAL DHOHO KEDIRI DI DESA BULUSARI TAROKAN KABUPATEN KEDIRI - Sindi Kania; A Zahid (Jurnal Neo Societal, 2024)
This research is research that has urgency regarding the lives of the people of Bulusari who are experiencing social and religious transfiguration due to the establishment of Dhoho Kediri International Airport (BIDK) as one of the infrastructure developments that requires an in-depth understanding of the effects on the local community. Fundamentally, transfiguration appears as a multiplier effect, meaning that it has an influence not only on one aspect, namely the economy, but infiltrates aspects outside it, namely social, cultural and religious. In this research, the researcher used a qualitative research model with a qualitative descriptive research design that can be viewed from the words or behavior of the Bulusari people who can express it as is without data manipulation through observation and interview techniques. Meanwhile, the analysis of the research study is linked to Herbert Alexander Simon's Theory of Bounded Rationality. The research results show that the socio-religious transfiguration of the Bulusari community can be viewed as the result of limited rationality in responding to and testing abilities and experience in dealing with environmental changes resulting from the establishment of Dhoho Kediri International Airport. Cognitive abilities, environmental factors and adaptation greatly influence how and in what manner individuals make decisions. Where every decision always produces causes and effects that affect oneself and others.